ANALISIS PROSEDUR PENYALURAN KREDIT DALAM UPAYA MENGURANGI RISIKO KREDIT BERMASALAH PADA BANK-BANK BUMN DIKOTA BANJARMASIN - Rory Handriano (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2018)
Abstract, This research was conducted to determine the lending policy applied by banks - state-owned banks in the city of Banjarmasin, by using the 5C (Character, Capcity, Capital, Colletral and Condition) principle in accordance with the provisions of Bank Indonesia in relation to customer eligibility in obtaining credit. The method used in this study is secondary data that is processed and analyzed qualitatively qualitative. Where in this study the subject of the study was all state-owned banks in Banjarmasin city, namely 4 banks. The conclusions of this study is the analysis of lending policies in each state-owned bank in the city of Banjarmasin is good in accordance with banking policies that apply the principle of 5C and the principle of prudence in lending, management of non-performing loans and policies on rescue and settlement of credit.